Endocytosis at the maternal-fetal interface: balancing nutrient transport and pathogen defense - Fan, Mingming; Wu, Hongyu; Sferruzzi-Perri, Amanda N.; Wang, Yan-Ling; Shao, Xuan (Frontiers in Immunology, 2024)
Endocytosis represents a category of regulated active transport mechanisms. These encompass clathrin-dependent and -independent mechanisms, as well as fluid phase micropinocytosis and macropinocytosis, each demonstrating varying degrees of specificity and capacity. Collectively, these mechanisms facilitate the internalization of cargo into cellular vesicles. Pregnancy is one such physiological state during which endocytosis may play critical roles. A successful pregnancy necessitates ongoing communication between maternal and fetal cells at the maternal-fetal interface to ensure immunologic tolerance for the semi-allogenic fetus whilst providing adequate protection against infection from pathogens, such as viruses and bacteria. It also requires transport of nutrients across the maternal-fetal interface, but restriction of potentially harmful chemicals and drugs to allow fetal development. In this context, trogocytosis, a specific form of endocytosis, plays a crucial role in immunological tolerance and infection prevention. Endocytosis is also thought to play a significant role in nutrient and toxin handling at the maternal-fetal interface, though its mechanisms remain less understood. A comprehensive understanding of endocytosis and its mechanisms not only enhances our knowledge of maternal-fetal interactions but is also essential for identifying the pathogenesis of pregnancy pathologies and providing new avenues for therapeutic intervention.